2019
DOI: 10.1039/c8cp07680d
|View full text |Cite
|
Sign up to set email alerts
|

Using van der Waals heterostructures based on two-dimensional blue phosphorus and XC (X = Ge, Si) for water-splitting photocatalysis: a first-principles study

Abstract: BlueP/SiC and BlueP/GeC vdW heterostructures are high-efficiency photocatalysts for water-splitting at pH 0 and 7, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 108 publications
4
38
0
Order By: Relevance
“…The redox potential of water splitting is dependent on the pH value. 36 At pH ¼ 00, the standard oxidation (O 2 /H 2 O) potential and reduction (H + /H 2 ) potential for water splitting are E oxi ¼ À5.67 eV and E red ¼ À4.44 eV. In Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The redox potential of water splitting is dependent on the pH value. 36 At pH ¼ 00, the standard oxidation (O 2 /H 2 O) potential and reduction (H + /H 2 ) potential for water splitting are E oxi ¼ À5.67 eV and E red ¼ À4.44 eV. In Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In general, the oxidation and reduction reaction for photocatalytic water splitting can be written as: E OX O2=H2O ¼ À5:67 eV þ pH Â 0:059 eV and E red H þ =H2 ¼ 4:44 eV þ pH Â 0:059 eV. 51 The photocatalysis of water splitting consists of transportation and separation of photogenerated charge carrier electrons from the material to H + /H 2 and holes to oxygen molecules. It has been reported that materials with a band gap value greater than 1.23 eV are suitable for photocatalytic water splitting.…”
Section: Resultsmentioning
confidence: 99%
“…The generalized gradient approximation (GGA) [42] of Perdew-Burke-Ernzerhof functional (PBE) was used to explain the electron exchange and correlation potential [43][44][45]. For the accurate electronic and optical properties, the Heyd-Scuseria-Ernzerhof (HSE06) method was utilized [46]. The Grimme correction method (DFT-D3) was explored to describe the weak dispersion for the vdW correction [47].…”
Section: Computing Methodsmentioning
confidence: 99%